Externalism, self-knowledge and explanation - Flockemann, Richard (Rhodes University, Faculty of Humanities, Department of Philosophy)
In recent years, much attention has been given to the question of whether content externalism is compatible with an account of self-knowledge maintaining that we have an epistemically privileged access to the content of our propositional mental states. Philosophers who maintain the two are incompatible (incompatibilists) have put forward two majors types of challenge, which I call - following Martin Davies - the Achievement and Consequence Problems, which aim to demonstrate that self-knowledge cannot be reconciled with externalism. These challenges have spawned a great deal of literature, and a diverse range of arguments and positions have emerged in response. In this dissertation, I intend to focus on examples of these different avenues of response, and show how none of them are adequate. In the first chapter, I lay the groundwork for the debate, setting up how externalism and self-knowledge are to be understood, and outlining both the incompatibilist challenges as well as the available responses to them. In the second chapter I examine these responses in more detail, concluding finally that the best available response is Tyler Burge's. Burge has two arguments that together establish his compatibilist position. First, he shows that even if externalism is true, our judgements about our occurrent thoughts are immunejrom error. This establishes that our judgements about our thoughts must be true. Second, he offers a transcendental argument for self-knowledge, arguing that our access to our mental states must be not only true, but non-accidentally true, in a way sufficient for genuine knowledge. This establishes that we possess the correct epistemic entitlement to our thoughts. In the third chapter, I argue Burge's arguments do not, in fact, give us good reason to suppose externalism and self-knowledge to be compatible. This, I argue, is because B urge relies upon a transcendental argument, which, in this context, cannot establish that we have self-knowledge if externalism is true. All it establishes, I argue, is that we do possess self-knowledge. And this is insufficient to establish that externalism and self-knowledge are compatible.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Burge, Tyler; Externalism (Philosophy of mind); Self-knowledge, Theory of; Philosophy of mind